Amycolatopsis aidingensis sp. nov., a Halotolerant Actinobacterium, Produces New Secondary Metabolites - Li, Rui; Wang, Meng; Ren, Zhen; Ji, Yang; Yin, Min; Zhou, Hao; Tang, Shu-Kun (Frontiers in Microbiology, 2021)
A novel actinobacterium, strain YIM 96748T, was isolated from a saline soil sample collected from the south bank of Aiding Lake in Xinjiang Province, northwest China. Phylogenetic analysis based on 16S rRNA gene sequences revealed that strain YIM 96748T is closely related to Amycolatopsis cihanbeyliensis BNT52T (98.9%) and Amycolatopsis jiangsuensis KLBMP 1262T (97.2%). DNA–DNA relatedness between strains YIM 96748Tand its closest type strain A. cihanbeyliensis BNT52T was 59.6%. The average nucleotide identity between strains of YIM 96748T and its neighbor strain was 88.97%. Based on genotypic and phenotypic characteristics, it is concluded that strain YIM 96748T represents a novel species of the genus Amycolatopsis whose name was proposed as Amycolatopsis aidingensis sp. nov. The type strain is YIM 96748T. To investigate the biosynthetic potential of producing secondary metabolites, the complete genome of YIM 96748T was sequenced and analyzed. The complete genome sequence of YIM 96748T consists of a 7,657,695 bp circular chromosome, comprising 7162 predicted genes with DNA G+C content of 70.21 mol%. Fifty-one putative biosynthetic gene clusters of secondary metabolites were found, including the antibacterial/antitumor agent TLN-05220, antibacterial agent nocardicin A, antifungal agent nystatin A1 and the osmolyte ectoine. The investigation of the secondary metabolites of Amycolatopsis aidingensis YIM96748 T led to the discovery of two new phenylpropyl acetates enantiomers, amycoletates A (1) and B (2), as well as five known compounds, 4-hydroxy phenethyl acetate (3), 2-p-acetoxyphenylethanol (4), (S)-ethyl indole-3-lactate (5), (R)-ethyl indole-3-lactate (6) and p-hydroxybenzoic acid (7). One of gene clusters 14, 36 and 43, which contain a single module of polyketide synthase, might be responsible for the biosynthesis of compounds 1 and 2 from compound 7 as a precursor. Further studies, including one strain many compounds approach and genetic modification are needed to explore novel compounds from this talented halophilic Amycolatopsis strain.